PENGARUH PERPUTARAN KAS, PERPUTARAN PIUTANG, DAN PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PADA TAHUN 2016-2017 - Andriani, Winda; Supriono, Supriono (Politeknik Sawunggalih Aji, 2022)
Profitability is the main goal to be achieved by a company. The aim of this research is to calculate and describe the influence of cash turnover, accounts receivable turnover, and inventory turnover on profitability in manufacturing companies listed on the IDX. The population in this research were all manufacturing companies listed on the Indonesia Stock Exchange in 2016-2017 which contained 155 companies. The sampling technique used in this research was systematic random sampling. Based on the formula of systematic random sampling to determine the number of research samples, obtained by the number of companies to be researched are as many as 31 companies. The result showed that (1) Partially, cash turnover has a significant negative effect of -4,242 on profitability in manufacturing companies listed on the IDX. (2) Partially, accounts turnover has a positive and not significant effect of 1,824 on profitability in manufacturing companies listed on the IDX. (3) Partially, inventory turnover has a positive and significant effect of 5,269 on profitability in manufacturing companies listed on the IDX. (4) Cash turnover, accounts receivable turnover, and inventory turnover have a simultaneous positive and significant effect on profitability in companies listed on the IDX, which is indicated by f count level of 14,220 > f table of 2,76, f test also shows a significance level of 0,000 smaller than alpha (0,05). Those results indicate that F count > F table and significance value smaller than alpha value (0.05).